ANALISIS DAMPAK TINGKAT SUKU BUNGA ACUAN TERHADAP FLUKTUASI NILAI TUKAR RUPIAH PADA TAHUN 2023 - Viona Sabilla Putri Armasa (Prodi Pendidikan Ekonomi Universitas Mulawarman, 2025)
This study aims to examine and analyze the impact of the benchmark interest rate on rupiah exchange rate fluctuations in 2023. This study used a quantitative approach. The type of data used is secondary data obtained from the Central Statistics Agency, Ministry of Trade, and Bank Indonesia within a monthly period in 2023. The analysis technique used is simple regression analysis. The results showed that the benchmark interest rate (BI Rate) significantly affected the exchange rate of the Rupiah against the US Dollar. Monetary policies that can maintain price stability include the money supply, interest rates and exchange rates. This reinforces the understanding that monetary policy, particularly interest rate adjustment is an effective tool in managing exchange rates and formulating monetary strategies that are responsive to global and domestic economic conditions to promote stable economic growth in Indonesian.